Challenges and future prospects for developing Ca and Mg water quality guidelines: a meta-analysis. (21st January 2019) - Bogart, Sarah J.; Azizishirazi, Ali; Pyle, Greg G.
Abstract : Anthropogenic activities have the potential to increase water hardness (Ca + Mg) in receiving waters to toxic concentrations, and thus, water quality guidelines (WQG) for Ca and Mg are warranted. However, Ca can modify Mg toxicity in Ca-poor water and additional interactions with other major ions (Na +, K +, HCO3 − /CO3 2−, SO4 2− and Cl − ) may occur, potentially obscuring the water hardness–effect relationship. In a meta-analysis of toxicological studies, we: (i) evaluate the performance of three WQG derivation methods, and (ii) determine the influence of several variables (acute/chronic data, anions, Ca:Mg ratios, non-geographically relevant species) on the models. We find that the most sensitive species- or species sensitivity distribution (SSD)-based WQG derivation methods greatly overestimate water hardness toxicity, particularly if non-resident species are included. Broad-scale implementation of most sensitive species- or SSD-based WQG is impractical because water hardness varies beyond and within the regional scale. Anion type does not affect water hardness toxicity across species, but the Ca : Mg ratio is toxicologically relevant, underscoring the importance of considering ion ratios when developing major ion WQG. Although data supporting formal water hardness WQG are unavailable, we suggest using a two-component background condition approach that supports simultaneous management of water hardness and Ca : Mg ratio, and WQG that are applicable beyond the regional scale. This article is part of the theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.